Comparison of Dark Personality Traits, Feeling of Alienation and Spiritual Well-Being in People with and without Tendency to Vandalism - Abbas Abolghasemi; Seyyedeh Zahra Seyyed Noori; Morteza Zakeri; Reza Ghorbani (روانشناسی بالینی و شخصیت)
Introduction: The aim of this study was to compare dark personality traits, feelings of alienation, and spiritual well-being between individuals with a tendency toward vandalism and those without.Method: This survey study employed a causal-comparative design. The population for this study consisted of all individuals residing in prisons within Guilan Province in the year 2020. The sample for the present study consisted of 380 prisoners, including 180 individuals with a history of vandalism and 200 without. These participants were identified and selected from among the prisoners residing in facilities within Guilan Province. To collect data, we utilized the Dark Personality Traits Questionnaire (Jennison & Webster, 2010), the Alienation Scale (Deen, 1961), and the Spiritual Well-being Scale (Golparvar et al., 2014).The research data were analyzed using statistical methods, specifically analysis of variance and the independent t-test.Results: The results indicated that prisoners convicted of vandalism exhibited higher levels of dark personality traits and feelings of alienation compared to those without vandalism convictions. Additionally, spiritual well-being was significantly lower among prisoners with vandalism (P < 0.01).Discussion and conclusion: These findings have significant implications for pathology, prevention, and the implementation of psychological, social, and spiritual training to address vandalism among prisoners and modify its contributing factors.